Flaubert - Winock, Michel (The Belknap Press of Harvard University Press, 2016)
Michel Winock situates Flaubert in France's century of great democratic transition. Wary of the masses, Flaubert rejected universal suffrage, but above all he hated the vulgar, ignorant bourgeoisie, a class that embodied every vice of the democratic age. His loathing became a fixation--and a source of literary inspiration.--